Serum EMMPRIN/CD147 promotes the lung pre-metastatic niche in a D2A1 mammary carcinoma mouse model - Feigelman, Gabriele; Simanovich, Elina; Rahat, Michal A. (Frontiers in Immunology, 2025)
Several types of cancer, including breast cancer, metastasize to the lung. However, before the disseminating tumor cells (DTCs) arrive there, the lung must be prepared as a hospitable environment for them, forming the pre-metastatic niche (PMN). It is now accepted that the primary tumor can release soluble mediators or extracellular vesicles that activate the PMN resident cells, recruit immune cells, promote angiogenesis, and remodel the extracellular matrix (ECM), even before the arrival of DTCs to the niche. However, not all the components of the tumor secretome are known. Here we demonstrate in a mouse model of breast cancer designed to generate lung PMN, that EMMPRIN, a multifunction protein and mediator of tumor-stroma cell interactions, is part of that secretome. To study the involvement of EMMPRIN in the generation of lung PMN, we knocked down its expression in D2A1 cells (D2A1-KD), treated the mice with the anti-EMMPRIN antibody developed in our lab (m161-pAb), or administered the recombinant EMMPRIN protein to healthy mice. We show that the primary tumor released elevated levels of EMMPRIN in mice implanted with paternal D2A1 cells (D2A1-WT), generating lung PMN by increasing VEGF, MMP-9 and TGFβ secretion, enhancing angiogenesis, activating fibroblasts, increasing neutrophils infiltration, and remodeling the ECM. These effects were inhibited in mice implanted with D2A1-KD cells or administered with m161-pAb. In healthy mice, the recombinant EMMRPIN recapitulated the effects of high EMMPRIN levels. Thus, EMMPRIN as part of the tumor secretome is sufficient to promote the lung PMN, and targeting it could potentially inhibit the metastatic cascade.